Timing of surgery for patients with infective endocarditis complicated by stroke. (3rd May 2023) - Tao, M; Manikantan, P; Despotidis, G; Alkhalil, A; Parikh, P; Pyo, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Infective endocarditis (IE) is a disease associated with high risk of morbidity and mortality. Recent literature suggests that early surgery may be performed without increased risk of mortality, however this association in patients with IE complicated by cerebral infarction (CI) remains unclear. Purpose: The purpose of this meta-analysis is to assess the association between early surgery after CI and mortality in patients with IE complicated by CI. Methods: We performed a literature search for studies reporting an association between early surgery and study endpoints. The primary endpoint was in-hospital mortality. The secondary endpoint was long-term mortality. Early surgery was defined as surgery within 14 days of CI event. Conventional therapy was defined as surgery after 14 days of CI event. The search included the following databases: Ovid MEDLINE, EMBASE, Web of Science, and Google Scholar. The search was not restricted to time or publication status. Results: A total of 6 studies with 747 participants (318 with early surgery vs 429 with conventional therapy) were included. The mean duration of follow-up was 36 months (ranging between 12 to 62 months). Early surgery was not associated with increased risk of in-hospital or long-term mortality compared to conventional therapy (OR 1.21, 95% CI 0.59, 2.49; P=0.6; OR 0.65, 95% CI 0.06, 7.22; P=0.72). Heterogeneity was moderate: Chi2 = 7.26, I2 = 45%. Conclusions: Early surgery within 14 days of CI is not associated with increased risk of in-hospital or long-term mortality in patients with IE complicated by CI. Early Surgery and In Hospital Mortality Early Surgery and Long Term Mortality